Economy and Social Status: Methods for Empirically Determining Status Effects on Ratio Satisfaction of Income - Sedlarski, Teodor (Research Papers, 2020)
This articles summarizes the empirical study methods of the social status comparisons effects on subjective material well-being. The possibility to empirically check hypotheses about the impact of social status on economic behavior enables the inclusion of status into modern mainstream economic analysis.